Foreign Direct Investment and the Single Market. - Neary, J (CEPR, 2002)
This Paper extends the theory of multinational corporations, identifying three distinct influences of internal trade liberalization by a group of countries on the level and pattern of inward foreign direct investment (FDI). First, the tariff-jumping motive encourages plant consolidation. Second, the export platform motive favours FDI with only a single union plant relative to exporting, and may induce a firm that has never exported to invest. Finally, reduced internal tariffs increase competition from domestic firms, which dilutes the other motives and may induce a 'Fortress Europe' outcome of multinationals leaving union markets even though external tariffs are unchanged.